IgG4-related hypertrophic pachymeningitis with ANCA-positivity: A case series report and literature review - Xia, Cheng; Li, Ping (Frontiers in Neurology, 2022)
Background Hypertrophic pachymeningitis (HP) is a rare inflammatory disorder characterized by local or diffuse thickening of the intracranial or spinal dura mater. The most frequent cause of HP is antineutrophil cytoplasmic antibodies (ANCA), followed by IgG4. However, few cases of IgG4-HP coexpressing ANCA have been reported. Herein, we present three cases of IgG4-HP coexpressing ANCA and review the relevant literature to document the overlap of these two HP causes as a potential clinical pattern. Methods We retrospectively analyzed three patients with IgG4-HP coexpressing ANCA in our center and consulted the PubMed database to find other relevant cases reported in English from 1976 to April 2022. We used the following keywords: pachymeningitis, meningitis, dura, antineutrophil cytoplasmic antibody, myeloperoxidase, and proteinase-3. We analyzed the clinical, serological, radiological, and pathological characteristics of the obtained cases based on the ACR and Chapel Hill criteria and the exponential moving average (EMA) algorism for ANCA-associated vasculitis (AAV) and the IgG4-RD Comprehensive Diagnostic Criteria. Results We analyzed a total of 10 cases: seven literature reports and our three patients (52- and 61-year-old women and a 65-year-old man). The IgG4-related disease (IgG4-RD) diagnoses were definitive in four cases, and probable and possible in three cases. Eight patients had ANCA against myeloperoxidase (MPO), and two had ANCA against proteinase-3 (PR3). Two patients had both IgG4-RD and AAV, while the others only had ANCA seropositivity without additional clinical or pathological markers of AAV. Conclusion With regard to HP, we reconfirmed the existence of the IgG4-RD and AAV overlap syndrome. Meanwhile, our review does not support the hypothesis that ANCA positivity in IgG4-RD results from an excessive B-cell response. We speculate that IgG4-RD and AAV have similar or associated pathogeneses, although uncovering the role of IgG4 and ANCA in these pathophysiological processes requires further investigation.